Revision of the genus Adiscus Gistel, 1857 (Coleoptera: Chrysomelidae, Cryptocephalinae) from mainland China - Duan, Wen-Yuan; Zhou, Hong-Zhang (Zootaxa, 2022)
The mainland Chinese fauna of the leaf beetle genus Adiscus Gistel, 1857 is revised and three new species described: Adiscus daofuensis Duan & Zhou, new species from Sichuan, Gansu and Henan, A. ningshanensis Duan & Zhou, new species from Shaanxi, and A. tanae Duan & Zhou, new species from Tibet. One species is newly recorded from China: A. pubiventris Medvedev, 2008. The mainland Chinese fauna of Adiscus is 35 species, almost all of which are redescribed. Color illustrations and line drawings are provided and a key to all 35 Chinese mainland species. Types of the new species are deposited in the Institute of Zoology, Chinese Academy of Sciences.